POLITICAL REALITY IN PRINT MEDIA (FRAMING ANALYSIS OF THE GOLONGAN KARYA PARTY, MALUKU PROVINCE, IN THE MORNING AMBON EKSPRES AND KABAR TIMUR DAILY) - Said Lestaluhu; La Jaali (Universitas Gunadarma, 2023)
This type of research is qualitative descriptive research focusing on framing the reporting of the Xth Deliberation of the Golongan Karya Party. This research will be conducted at the Ambon Ekspres Morning Daily Media and the Kabar Timur Daily as the object of research; the research plan will be carried out in July 2020. The author uses two data sources, namely primary data from news texts about the Xth deliberation of the Golongan Karya Party, Maluku Province, by Daily Morning Ambon Ekspres and Kabar Timur editions of February 28 - March 09, 2020. Data analysis used in this study used the Robert Entman framing model analysis. This model divides into four ways: Define problems, Diagnose Causes, Make Moral Judgments and make Treatment Recommendations. The study results show that the Ambon Morning Express Daily is a framing process carried out through reporting, which tends to elevate the deliberation process to the Xth of the Golkar Party, Maluku Province, as a political event. It tends to highlight facts about the support of all DPD II and wing organizations as owners of voting rights who have given a mandate to Ramly Umasugi in his candidacy as Chair of the Maluku Golkar Party DPD. Ramly is imaged as one of the best cadres of the Golkar Party who has so far been successful in making Buru Regency a voice granary for the Golkar Party in Maluku, which is expected to become later an example of Golkar's progress at the provincial level